Strategi keuangan, corporate governance, dan nilai perusahaan: Peran mediasi profitabilitas - Gita Purwanda; Umi Muawanah (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose - This research examines the influence of Financial Strategy (Working Capital and Capital Structure) and Corporate Governance on Firm Value, with profitability as an intervening variable. Method - The research was conducted on companies listed in the Kompas 100 Index on the Indonesia Stock Exchange during 2021-2022. Samples were selected using purposive sampling and analyzed using path analysis. Findings - The Results reveal significant positive effects of Working Capital Management, Capital Structure, and Corporate Governance on Profitability. This underscores the potential of a well-crafted financial strategy to enhance profitability. Conversely, working capital management and corporate governance significantly negatively impact Firm Value, while Capital Structure and Profitability demonstrate significant positive influences. Profitability effectively mediates the relationship between Working Capital, Capital Structure, Corporate Governance, and Firm Value. Implications - These findings have significant practical implications. They serve as a valuable reference for management, providing insights on how to optimize financial decisions and governance to maximize firm value. For investors, this research offers important indicators for evaluating investment prospects, empowering them to make informed decisions.